Gut dysbiosis associated with the rats' responses in methamphetamine‐induced conditioned place preference. (22nd October 2020) - Yang, Cheng; Fu, Xiaoya; Hao, Wei; Xiang, Xiaojun; Liu, Tieqiao; Yang, Bao‐Zhu; Zhang, Xiaojie
Abstract: Methamphetamine (MA) is a potent stimulant and notoriously addictive. Individuals respond to MA effects differently and thus have a varying susceptible risk of developing MA use disorder. Cumulative evidence has indicated that gut dysbiosis contributes to behavioral response to drug effects. However, the role of gut microbiota in the susceptible risk of developing MA use disorder has remained elusive. Using an MA‐induced conditioned place preference (CPP) rat model, we administrated the same dose of MA to rats, which then showed distinct preferences in drug‐related place, indicating their different responses to MA. From all of the MA‐exposed rats, the eight with the highest CPP scores were labeled as group high CPP (H‐CPP), and the eight with the lowest were labeled as group low CPP (L‐CPP). By 16S ribosomal RNA (rRNA) sequencing, we found that the gut microbiota compositions differed between H‐CPP and L‐CPP. Specifically, Akkermansia was significantly higher in H‐CPP and positively correlated with the CPP scores. Notably, H‐CPP and L‐CPP differed in the gut microbiota composition prior to the CPP training; Ruminococcus was the dominant phylotype in H‐CPP at baseline. More importantly, rats pretreated by antibiotics showed a significantly stronger MA‐induced CPP than did the controls. Our study demonstrates that the gut dysbiosis was associated with the MA‐induced CPP, indicating that the gut microbiota might be important modulators for MA‐induced behavior and vulnerability to MA use disorder. Abstract : We established a methamphetamine‐induced CPP rat model to investigate the association between gut microbiota and rats' preference for methamphetamine. By 16S rRNA sequencing analysis, we found gut microbiota compositions differed between high CPP group and low CPP group before and after methamphetamine‐induced CPP training. More importantly, rats pretreated by antibiotics showed a significantly stronger methamphetamine‐induced CPP than did the controls.